DESAIN KARAKTER “STU” SEBAGAI KARAKTER PELENGKAP UNTUK MEMPERKUAT INTERAKSI TERHADAP MASKOT “XODE” BINUS DKV: “STU” Character Design as a Complementary Character to Strengthen Interaction with the “XodE” BINUS DKV Mascot - Retno Widya Hapsari; Ahmad Faisal Choiril Anam Fathoni (Universitas Trisakti, 2025)
“STU” Character Design as a Complementary Character to Strengthen Interaction with the “XodE” BINUS DKV Mascot. Mascots play a significant role in representing organizations by serving as visual identities that engage audiences emotionally and promote institutional values. BINUS School of Design (BINUS DKV) introduced its primary mascot “XodE” in 2022 to embody creativity, enthusiasm, and the dynamic spirit of its students and faculty. However, as a single character, XodE’s personality and emotional depth were limited without interactions to reveal more relatable traits. To address this limitation, the design of “STU” as a complementary mascot was initiated to enrich XodE's character through dynamic interactions and highlight the diverse personalities within the BINUS DKV community. Using the Design Thinking methodology, which includes stages such as empathy, definition, ideation, prototyping, and testing, the development of “STU” prioritized creating a visual and emotional counterbalance to “XodE”. “STU” was designed with rounded shapes and soft lines through this method to visually communicate his reserved, diligent, and introverted personality, contrasting XodE’s vibrant and expressive traits. The result is a companion character that enhances XodE’s personality through contrasting interactions and strengthens the emotional connection with the audience. This study demonstrates the importance of complementary character design in building engaging mascots that reflect organizational identity while fostering emotional resonance. The findings contribute to character design by illustrating how contrasting personalities and visual elements can enrich mascot narratives and deepen audience engagement.